2014
DOI: 10.1587/transinf.e97.d.1017
|View full text |Cite
|
Sign up to set email alerts
|

Rule-Based Verification Method of Requirements Ontology

Abstract: SUMMARYThere have been many researches about construction and application of ontology in reality, notably the usage of ontology to support requirements engineering. The effect of ontology-based requirements engineering depends on quality of ontology. With the increasing size of ontology, it is difficult to verify the correctness of information stored in ontology. This paper will propose a method of using rules for verification the correctness of requirements ontology. We provide a rule description language to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The systematic review identified the primary studies on the use of ontologies in RE [26], finding there are empirical evidences to state that ontologies benefit RE activities in both academy and industry settings, helping to reduce ambiguity, inconsistency and incompleteness of requirements and providing tool support and usage of W3C recommended ontology languages. Various ontology-based frameworks [27], models [28] and methods [29] have been proposed in order to support different RE phases, some even building a domain ontology for requirements classification, so-called Requirements Classification Ontology (RCO) [30]. Whichever purposes and RE phases the proposed ontology serves, it should be designed by using a proper ontology engineering method (e.g.…”
Section: B Ontologies For Requirements Engineeringmentioning
confidence: 99%
“…The systematic review identified the primary studies on the use of ontologies in RE [26], finding there are empirical evidences to state that ontologies benefit RE activities in both academy and industry settings, helping to reduce ambiguity, inconsistency and incompleteness of requirements and providing tool support and usage of W3C recommended ontology languages. Various ontology-based frameworks [27], models [28] and methods [29] have been proposed in order to support different RE phases, some even building a domain ontology for requirements classification, so-called Requirements Classification Ontology (RCO) [30]. Whichever purposes and RE phases the proposed ontology serves, it should be designed by using a proper ontology engineering method (e.g.…”
Section: B Ontologies For Requirements Engineeringmentioning
confidence: 99%